Cell fate following radiation of MDA-MB-231 and MCF-7 breast cancer cells pre-exposed to a tetrahydroisoquinoline analogue - Mercier, Anne Elisabeth (University of Pretoria, 2021)
Dissertation (MSc (Human Physiology))--University of Pretoria, 2021.